Some shocking aspects of EMU enlargement - Michael Frenkel; Christiane Nickel; Günter Schmidt (Deutsche Bank Research, 1999)
This paper uses a structural vector autoregression to examine differences in demand and supply shocks and the response to these shocks between EMU member countries and three other groups of countries. The first group includes non-EMU EU countries, the second group EFTA countries and the third group central and eastern European countries which seek EU membership over the next years. Our results suggest that, so far, EMU enlargement towards central and eastern European countries would involve significantly higher costs than EMU enlargement towards countries of the other two groups.
Keywords: F33; 330; European Monetary Integration; International Monetary Arrangements and Institutions; Europäische Wirtschafts- und Währungsunion; Schock; Wirtschaftliche Anpassung; Soziale Kosten; EU-Erweiterung; Schätzung; EU-Staaten; EFTA-Staaten; Ostmitteleuropa